A Systematic Review of Diagnostic Accuracy: Serological and Molecular Tests Compared to Culture for Invasive Fungal Infections - Dhuha A. Athouf; Hawraa A. Mohammed; Fatima Assad Baker (Indonesian Journal of Microbiology, 2026)
Invasive fungal infections (IFIs) remain a major clinical challenge, particularly among immunocompromised patients, due to their high morbidity, mortality, and diagnostic complexity. Despite being the gold standard, traditional fungal culture has low sensitivity and takes a long time to produce results. Recently, serological and molecular diagnostic approaches have emerged as potential alternatives to earlier and more precise IFI detection. The goal of this systematic review was to evaluate the effectiveness of various non-culture approaches and their potential impact on diagnostic precision. To detect invasive fungal infections (IFIs), this systematic review compared the diagnostic accuracy of commonly used genetic and serological approaches to fungal culture. A thorough literature search yielded eligible studies testing assays including β-D-glucan, galactomannan, cryptococcal antigen, and PCR-based approaches. A random-effects model was employed to calculate pooled sensitivity and specificity. While several serological techniques demonstrated good specificity and consistency across numerous fungal species, molecular assays were often more sensitive than culture, particularly for early detection. Despite variations in research quality and inconsistency in diagnostic thresholds, the data show that combining serological and molecular approaches significantly improves diagnosis accuracy and may reduce delays associated with culture-based identification. This systematic review demonstrates that for the diagnosis of invasive fungal infections, both molecular and serological diagnostic procedures outperform culture-based approaches. Molecular assays are important for early diagnosis due to their high sensitivity and rapid turnaround time. Serological tests are highly specific and reliable when performed correctly.